Optimal Unemployment Insurance in Search Equilibrium - Fredriksson, Peter; Holmlund, Bertil (Journal of Labor Economics, 2001)
Should unemployment benefits be paid indefinitely at a fixed rate or should the rate decline (or increase) over a worker’s unemployment spell? We examine these issues using an equilibrium model of search unemployment. The model features worker‐firm bargaining over wages, free entry of new jobs, and endogenous search effort among the unemployed. The main result is that an optimal insurance program implies a declining benefit sequence over the spell of unemployment. Numerical calibrations of the model suggest that there may be nontrivial welfare gains associated with switching from an optimal uniform benefit structure to an optimally differentiated system.